Allies and enemies: the Gülen movement and the AKP. Issue 1 (2nd January 2022) - Martin, Natalie
Abstract: This paper charts how the Gülen movement (GM)'s allegiance and effectiveness has changed over the past two decades. It examines how the GM has moved from being a fellow Islamist actor in Turkish politics to close ally during the first ten years of the AKP government with the joint aim of decreasing the Kemalist hold on the establishment. The paper then examines how the GM has been delegitimised by the AKP since it became more of a risk than an asset amidst disagreements over policy direction. It argues that the GM has transitioned from being a rival to an ally of the AKP in order to facilitate policy; going from a non-state actor pre-2002 to a quasi-state actor during its alliance. The alliance was a mutually beneficial 'marriage of convenience' which enabled both parties to consolidate power often through illiberal means. However, since 2013 the AKP-Gülen relationship has deteriorated markedly and the movement is now an enemy of the AKP and a victim of the same authoritarian drift it was previously complicit in.